New taxa of Peliosanthes and Tupistra (Asparagaceae) in the flora of Laos and Vietnam and supplemental data for T. patula - Nguyen, Khang Sinh; Averyanov, Leonid V.; Тanaka, Noriyuki; Konstantinov, Eugene L.; Maisak, Tatiana V.; Nguyen, Hiep Tien (Phytotaxa, 2017)
Three new taxa, Tupistra gracilis, Peliosanthes griffithii var. breviracemosa and P. hirsuta, are described and illustrated. The first two taxa are local endemics of northern Vietnam and the last species is endemic to karstic limestone areas of central Laos. Tupistra fungilliformis and P. yunnanensis are recorded for the first time for Vietnam. A recently described species T. patula from northern Vietnam is supplemented with new data on its morphology, ecology and distribution.